The Art of Multiculturalism Bharati Mukherjee's Imaginal Politics for the Age of Global Migration - Benedikter, Roland (SpringerBriefs in Sociology,, 2018)
This book describes what an "art of multiculturalism" could be and how in turn multiculturalism could be conceived as a form of art. It focuses on the early and middle work of Indian-born U.S. writer Bharati Mukherjee, in particular on her understanding of the "fusion" of literature and painting as a tool to inspire the creation of a "new global society" by empowering minorities through fostering and multiplying "differences in unity" and "unities in difference". The book includes, in condensed ways, an explanation of Mukherjee's use of ancient Indian painting techniques for postmodern writing; and it provides a short introduction to the relation between multiculturalism, postmodernity and "imaginal politics". The book is written in an easy to read style accessible to all interested in the topic: high school and university students and teachers; those generally interested in the interface between literature, the arts and politics; and specialists in multicultural studies and global and international studies. The book is particularly suited to use in teaching. .